Effect of front double wishbone strut position on vehicle steering and suspension performance - Mat Darus, Intan Zaurah (2012)
The front double wishbone suspension parameters are related as a multi-body model. By replacing the new suspension and steering hard points, the performance of the suspension system is studied using CATIA and MSC ADAMS software for modeling and analyzing, respectively. In this case two tests were done, steady state circular test in ADAMS/View and parallel wheel travel in ADAMS/Car. The strut position is directly related to Kingpin inclination angle and scrub radius. The increase the amount of these two parameters has an effect on steering performance in low speed and negative displacement, such as camber, caster and Kingpin inclination angles in negative displacement of wheels. Moreover, the same tests in rear double wishbone suspension show that the growth has no effect on camber, caster and Kingpin inclination angles. So, the major effect of this geometry is on the front independent suspension. In this project, the details were selected on electric vehicle (EV) for kinematics analysis.